2004
DOI: 10.1242/jcs.01074
|View full text |Cite
|
Sign up to set email alerts
|

Cross-linking ATP synthase complexes in vivo eliminates mitochondrial cristae

Abstract: We have used the tetrameric nature of the fluorescent protein DsRed to cross-link F1FO-ATPase complexes incorporating a subunit γ-DsRed fusion protein in vivo. Cells expressing such a fusion protein have impaired growth relative to control cells. Strikingly, fluorescence microscopy of these cells revealed aberrant mitochondrial morphology. Electron microscopy of cell sections revealed the absence of cristae and multiple layers of unfolded inner mitochondrial membrane. Complexes recovered from detergent lysates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
47
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(54 citation statements)
references
References 46 publications
(74 reference statements)
6
47
0
Order By: Relevance
“…Mitochondria often undergo ultrastructural remodeling to tailor energy output to meet the demands on the cell and their number can vary between cells of the same tissue [68][69][70][71]. The "megamitochondria" we observed have disruptions in their cristae architecture, a condition which was previously noted with cross-linking ATP synthase complexes [72,73]. A general trend in cells of older organisms is a decrease in number and increase in size of the mitochondrial population [70,74].…”
Section: Discussionsupporting
confidence: 52%
“…Mitochondria often undergo ultrastructural remodeling to tailor energy output to meet the demands on the cell and their number can vary between cells of the same tissue [68][69][70][71]. The "megamitochondria" we observed have disruptions in their cristae architecture, a condition which was previously noted with cross-linking ATP synthase complexes [72,73]. A general trend in cells of older organisms is a decrease in number and increase in size of the mitochondrial population [70,74].…”
Section: Discussionsupporting
confidence: 52%
“…F 1 F O ATP synthase was homogeneously distributed along the cristae membranes. The enrichment of F 1 F O ATP synthase in positively curved membrane parts of cristae was observed before (Parsons, 1963;Strauss et al, 2008;Bieling et al, 2010;TrutaFeles et al, 2010), and ATP synthase dimerization probably a main determinant of cristae shaping (Paumard et al, 2002;Gavin et al, 2004;Minauro-Sanmiguel et al, 2005;Strauss et al, 2008;Davies et al, 2012). Unfortunately, the limited degree of immunogold labeling does not render the explicit confirmation of F 1 F O ATP synthase dimers possible.…”
Section: Discussionmentioning
confidence: 96%
“…mitochondrial DNA propagation/expression, remain unaffected in these mutant strains. An alternative point of view suggests that the ATP synthase in some way regulates cristae formation, a question that is currently being studied by several laboratories (47)(48)(49)(50)(51). A link between ATP synthase and cristae biogenesis was first suggested by Allen et al (52), based on electron microscopy analyses of Paramecium multimicronucleatum mitochondria.…”
Section: Ultrastructural and Immunocytochemical Analyses Of The ⌬Fmc1mentioning
confidence: 99%
“…In favor of this hypothesis, it was found that loss of ATP synthase subunit e or g, both of which appear to be specifically involved in the enzyme dimerization in yeast (54), results in abnormal mitochondrial morphologies characterized by numerous digitations and onion-like structures that correspond to an uncontrolled biogenesis and/or folding of the inner membrane (47). Moreover, a recent report from the Devenish laboratory (49) shows that the correct arrangement of F 1 F O -ATP synthase complexes within the inner membrane is crucial for the genesis and/or maintenance of mitochondrial cristae and morphology. Our examination, at the cellular level, of yeast mutants that fail to assemble the ␣ 3 ␤ 3 oligomer reinforces the notion that the ATP synthase is a key determinant in the biogenesis of the inner membrane.…”
Section: Ultrastructural and Immunocytochemical Analyses Of The ⌬Fmc1mentioning
confidence: 99%